Universality of ac conduction for generalized space-charge transport in ordered solids - Gommans, Hendrikus Hubertus Petrus; Kemerink, Martijn; Schilders, Wil (Physical review. B, Condensed matter and materials physics, 2005)
On numerous nonmetallic systems, the ac conductivity is observed to follow an approximate power law behavior σ(ω)=ωs with 0<s⩽1. We show that the presence of nonlimiting, i.e., ohmic, contacts on the sample necessarily leads to these characteristics. The ac conductivity curves are obtained by the numerical solution of the complete set of time-dependent drift-diffusion equations. The calculated ac conductivity curves can be converted into quasiuniversal master curves by application of the Taylor-Isard scaling law for an arbitrary temperature dependence of the mobility. Our results demonstrate that space-charge transport can lead to the commonly observed power law and scaling behaviors without incorporating disorder. Nevertheless, the implications of disorder are discussed and they are expected to increase the range over which the power law behavior extends.